Право людини на репродуктивне відтворення: постмортальне використання, зберігання кріоконсервованих матеріалів - Ходєєва, Н. В.; Khodieieva, N. V.; Наталія Ходєєва (Вісник Харківського національного університету внутрішніх справ. – 2025. – № 1 (108), ч. 1. - С. 123-135, 2025)
Проведено аналіз чинного законодавства України та доктринальних підходів щодо права людини на репродуктивне відтворення в розрізі права на постмортальну репродукцію щодо правомочностей використання та зберігання кріоконсервованих матеріалів. Надано визначення терміна «постмортальна репродукція». Здійснено аналіз застосування постмортальної репродукції, сурогатного (замінного) материнства. Зроблено висновок щодо чіткої регламентації осіб, які можуть бути наділені правом на постмортальну репродукцію, визначено строк, протягом якого проведення постмортальної репродукції є неможливим.

The article analyses the current legislation of Ukraine and doctrinal approaches to the human right to reproduction in the context of the right to postmortem reproduction in terms of the right to use cryopreserved materials and their storage, taking into account changes in Ukrainian legislation and the experience of European countries. The author analyses the ways of regulating the right to postmortem reproduction, taking into account the experience of medical practice (drawing up an application-permission or an agreement with a healthcare facility on the storage and use of cryopreserved materials). The author concludes that it is necessary to establish a period of one calendar year from the date of death of a partner, during which post-mortem reproduction will not be possible; that assisted reproductive technologies may be used by partners; that the current legislation of Ukraine should enshrine the possibility of a man in the event of death or declaration of a partner’s death by a court and the possibility of a woman in the event of loss of reproductive function (the ability to bear and give birth to a child) in the presence of a cryopreserved embryo (zygote, blastula) and an application for permission or an agreement with a healthcare facility on the storage and use of cryopreserved materials – the right to use surrogacy (substitute) motherhood services, but taking into account the period of one calendar year from the date of death of the partner, during which postmortem reproduction will not be possible, as well as the possibility of storing cryopreserved embryos, if they are transferred for storage by a serviceman and his partner, also free of charge for three years from the date of death of such a person or declaration of death by a court, with the provision for further storage of cryopreserved embryos at the expense of the spouse or other person specified in the order (for storage of own cryopreserved embryos).
The human right to reproduction: postmortem use and storage of cryopreserved materials
Keywords: репродуктивні технології; постмортальна репродукція; сімейні відносини; права подружжя; статеві клітини; кріоконсервовані матеріали; використання (зберігання); строк; сурогатне материнство; національне та міжнародне законодавство; reproductive technologies; postmortem reproduction; family relations; spouses’ rights; germ cells; cryopreserved materials; use (storage); term; surrogacy; national and international legislation